Fundamental tradeoff between emission intensity and efficiency in light-emitting electrochemical cells - Reenen, Stephan van; Janssen, René A. J.; Kemerink, Martijn (Advanced functional materials, 2015)
The characteristic doping process in polymer light-emitting electrochemical cells (LECs) causes a tradeoff between luminescence intensity and efficiency. Experiments and numerical modeling on thin film polymer LECs show that, on the one hand, carrier injection and transport benefit from electrochemical doping, leading to increased electron-hole recombination. On the other hand, the radiative recombination efficiency is reduced by exciton quenching by polarons involved in the doping. Consequently, the quasi-steady-state luminescent efficiency decreases with increasing ion concentration. The transient of the luminescent efficiency shows a characteristic roll-off while the current continuously increases, attributed to ongoing electrochemical doping and the associated exciton quenching. Both effects can be modeled by exciton polaron-quenching via diffusion-assisted Förster resonance energy transfer. These results indicate that the tradeoff between efficiency and intensity is fundamental, suggesting that the application realm of future LECs should be sought in high-brightness, low-production cost devices, rather than in high-efficiency devices.
Gesehen am 05.12.2019